2011
DOI: 10.1128/jcm.05396-11
|View full text |Cite
|
Sign up to set email alerts
|

Clostridium botulinum Group I Strain Genotyping by 15-Locus Multilocus Variable-Number Tandem-Repeat Analysis

Abstract: Clostridium botulinum is a taxonomic designation that encompasses a broad variety of spore-forming, Gram-positive bacteria producing the botulinum neurotoxin (BoNT). C. botulinum is the etiologic agent of botulism, a rare but severe neuroparalytic disease. Fine-resolution genetic characterization of C. botulinum isolates of any BoNT type is relevant for both epidemiological studies and forensic microbiology. A 10-locus multiple-locus variable-number tandem-repeat analysis (MLVA) was previously applied to isola… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
24
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 31 publications
1
24
0
Order By: Relevance
“…MLVA is thus a DNA typing technique that is simple, rapid, and highly reproducible. Although earlier studies using MLVA have extensively examined pathogens such as Staphylococcus aureus (Sabat et al, 2003), Listeria monocytogenes (Murphy et al, 2007;Miya et al, 2008), and C. botulinum (Fillo et al, 2011), reports on food spoilage organisms other than Geobacillus species (Seale et al, 2012) and Bacillus licheniformis (Dhakal et al, 2013), which are isolated from milk powders, are scarce.…”
Section: Introductionmentioning
confidence: 99%
“…MLVA is thus a DNA typing technique that is simple, rapid, and highly reproducible. Although earlier studies using MLVA have extensively examined pathogens such as Staphylococcus aureus (Sabat et al, 2003), Listeria monocytogenes (Murphy et al, 2007;Miya et al, 2008), and C. botulinum (Fillo et al, 2011), reports on food spoilage organisms other than Geobacillus species (Seale et al, 2012) and Bacillus licheniformis (Dhakal et al, 2013), which are isolated from milk powders, are scarce.…”
Section: Introductionmentioning
confidence: 99%
“…In 2005, Francois and colleagues [30] reported on the use of automated microfluidic electrophoresis with the Agilent 2100 bioanalyzer 'lab-on-achip' for the VNTR typing of S. aureus isolates. Since then, there have been a growing number of studies that have shown the clear advantage of microfluidic chips over the standard agarose gels for the MLVA/MLVF typing in terms of electrophoretic separation resolution, reproducibility, rapidity and automated data analysis [31,32].…”
Section: Variable-number Tandem Repeat (Vntr) Typingmentioning
confidence: 99%
“…The analysis was extended to B and F toxin serotype strains, in addition to A serotype strains: five newly characterised MLVA loci were added to the previous 10-MLVA scheme and new groups were described. To date, MLVA data have been obtained for about 300 international C. botulinum strains, whereas profiles from 79 strains across Europe have been published [40].…”
Section: Irelandmentioning
confidence: 99%